Potential of Bacillus spp. isolated from food waste compost for controlling rice diseases - Usmana Meehae,; Aunkamol Kumngen,; Wilaiwan Chotigeat,; Sudarat Suwannarat,; Sujunya Anuchan,; Sukhuman Whankaew,; Siwapong Leunram,; Seppo Karrila,; Jutarut Iewkittayakorn, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bacterial leaf blight, bakanae and blast are severe, economically damaging rice diseases caused by Xanthomonas oryzae, Fusarium fujikuroi, and Magnaporthe oryzae, respectively. Bacillus spp. have been applied as bioactive, eco friendly agents to control these diseases. In this study, five antagonistic strains isolated from food waste compost, namely B. subtilis strain BS, B. amyloliquefacien strain C2-1, B. tequilensis strain 1-BA, B. licheniformis strain 2-BA, and Lysinibacillus. sp strain 3-BA were tested for their efficacy against rice diseases. The inhibition of X. oryzae was tested by paper disc diffusion, while the inhibitions of F. fujikuroi and M. oryzae were tested in dual cultures. It was found that B. amyloliquefacien strain C2-1 gave the widest clear zones. At 24 h, 48 h, 72 h and 7 days, the strain had produced zones of inhibition against X. oryzae of 7.41±0.65, 7.9±0.20, 8.8±0.65 and 8.90±0.12 mm, respectively. B. amyloliquefacien strain C2-1 also reduced the growth of the fungal rice pathogens F. fujikuroi and M. oryzae, achieving 98.79% and 97.74% inhibitions, respectively. B. amyloliquefaciens strain C2-1 was also effective against X. oryzae, F. fujikuroi, and M. oryzae in the greenhouse. Fourteen days after spraying rice plants with the B. amyloliquefacien strain C2-1, infections with X. oryzae, F. fujikuroi, and M. oryzae were inhibited by 60%, 37%, and 25%, respectively. The results suggested that B. amyloliquefacien strain C2-1 can be used as a biocontrol agent against bacterial leaf blight, bakanae, and rice blast diseases.